AUTHENTICATION OF THE FIRST SIGHTING OF THE BLACK STORK (CICONIA NIGRA LINNAEUS, 1758) IN THE WESTERN ALGERIAN STEPPES (NAAMA REGION) - Youcefi Ahmed Toufik*; Haddi Leila**; Litim Kouider**; Gouacem Ali** (Natural Resources and Sustainable Development)
The Naama region is a vast territory that hosts several birds of different phenology, including migratory birds which find favorable conditions for wintering or transiting. This manuscript attempts to authenticate the presence of a rather rare species of black stork (Ciconia nigra Linnaeus, 1758), which is recorded for the first time in this area of the western steppes. This species has identified and photographed itself in the area of application near the Mécheria wastewater treatment plant. The phenology of this specie in the observation area can be classified as a passing visitor. The stopover of the black stork in this area may be due to the conditions of the habitat, which are manifested by the high level of soil moisture that encourages biodiversity and promotes the appearance of an imprinting food chain, serving as a food for migratory birds.